The Analysis of Strategic Management Based on Digital Transformation and Entrepreneurship - Kusmarini Kusmarini; Miliyanti Br Pinem; Amisa Fatel Samosir; Ritta Ardiati; Hani Herlianti; Kuswanto Kuswanto; Sri Wahyuni; Ahmad Soleh (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Digital transformation has shifted the paradigm of strategic management from a conventional approach to one that is more adaptive, innovative, and technology-based, particularly in the context of entrepreneurship and MSME development. This article aims to analyze the development of strategic management studies based on digital transformation and entrepreneurship, as well as to identify trends, key findings, and research gaps that remain open. The research uses a Systematic Literature Review (SLR) method, examining 25 scholarly articles sourced from Google Scholar and SINTA within the 2020-2025 timeframe. The selection process was based on inclusion and exclusion criteria that emphasize topic relevance, publication timeliness, and the quality of peer-reviewed journals. The synthesis results show that digital transformation plays a significant role in improving operational efficiency, expanding market reach, strengthening innovation, and creating sustainable competitive advantages. Key factors influencing successful strategy implementation include digital capabilities, strategic innovation, organizational culture, regulatory support, and the readiness of infrastructure and human resources. However, most studies are still conceptual and lack strong empirical testing. This article concludes that the success of strategic management in the digital era heavily depends on an organization’s ability to integrate technology, innovation, and sustainability holistically to respond to increasingly complex business environment dynamics.